A new strategy for high-value reutilization of recycled carbon fiber: Preparation and friction performance of recycled carbon fiber felt-based C/C-SiC brake pads. Issue 13 (September 2019) - Guo, Wenjian; Bai, Shuxin; Ye, Yicong; Zhu, Li'an; Li, Shun
Abstract: To achieve the high-value reutilization of recycled carbon fiber (rCF), a new strategy of preparing rCF-based C/C-SiC brake pads is proposed in this work. The results show that the rCF possesses crystal structure and tensile strength comparable with those of virgin CF (vCF) exception of pyrolytic char adhering to the surface of rCF after pyrolysis. The rCF was converted into C/C composites through impregnation-pyrolysis. Pyrolytic char was found to have no evident negative effect on the densification rates of the rCF C/C composites. By reactive melt infiltration, the rCF C/C-SiC composites were fabricated based upon the rCF C/C composites. The achieved rCF C/C-SiC composites do not differ markedly from the vCF group control in terms of microstructure and bending strength. Furthermore, the thermal diffusion coefficients of the rCF C/C-SiC composites are very close to those of vCF C/C-SiC composites in the temperature range 25°C-300 °C. The coefficient of friction values of the rCF C/C-SiC composites are as stable as those of vCF control group, both being maintained at approximately 0.4 during friction test, whether at 25 °C or 300 °C. The wear rate of the rCF C/C-SiC composites is 3.8 μm·min −1, nearly indistinguishable from that of the vCF C/C-SiC composites, i.e., 4.5 μm·min −1, further suggesting that the two materials resemble each other closely. The rCF C/C-SiC composites exhibit great potential for use as alternative brake pads to serve auto braking systems. This work opens up a new path for high-value reuse of rCF.